(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Corpora have become essential tools in comparative translation studies, enabling researchers to analyze linguistic patterns, translation strategies, and cross-linguistic influences. By comparing parallel and comparable corpora, scholars can identify how different languages handle translation challenges, from idiomatic expressions to syntactic structures. This article examines the use of corpora in comparative translation studies, with particular attention to the contributions of scholars like Mona Baker, Anthony Pym, and Sara Laviosa. Their work has advanced the field, offering insights into translation universals and the dynamics of cross-linguistic interaction. The article outlines methodologies for using corpora in translation studies and discusses the impact of corpus-based research on translation theory and practice.